All Optical Limiter Based on Self Phase Modulation and Dispersive Chirping - Holtmannspötter, Michael; Schmauß, Bernhard (Cleo Juni 2007, 2007)
All optical limiters may constitute the enablers of 3R regeneration for bit rates of 40 Gb/s and above. In M. Daikoku et al. (2006), an all optical limiter is used to enhance the robustness of a cross saturation-based 3R regenerator against surge conditions, whilst in C. Kouloumentas et al. (2006), the limiter equalizes the output of a Fabry Perot filter feeding a clock recovery unit. Furthermore, all optical limiters could mitigate fast power transients caused by data traffic bursts in optical amplifiers (OA). Their suitability for fast events is due to the exploitation of nonlinear optical effects, which are practically instantaneous. We investigated an all optical limiter based on self phase modulation (SPM). The limiter consists of a highly nonlinear fibre (HNLF), two dispersion compensating fibres and an optical band pass filter. Low threshold is achieved by center frequency filtering (CFF) of the SPM-broadened signal spectrum. Negative dispersive chirping optimizes the power transfer characteristic for very low fluctuations in output pulse peak power. Simulations were conducted with and without a fibre transmission span, consisting of 80km of standard single mode fibre (SSMF), the dispersion was compensated by a DCF. The signals were reamplified by an OA. The simulation results of the back-to-back case and the transmission case nearly did not differ. The moderate distortions induced by the limiter in both cases demonstrate the limiter's potential for practical application.
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.LEH.allopt